Truth of terrorism - Tarin, Hanif (New Delhi, 2009)
he present collection of poems is the author's book of pain and humanity's book of torture. It contains civilized protest against death, torture and tyranny unleashed by the practitioners of brutal super powerism in the lands of olives-The symbols of peace and amity. Moved by the carnage in Iraq, Palestine and other Muslim lands, the poet wails out 'The Swallows have not come.
Keywords: Terrorism; Violence; Criminology